Ecological Study of Aquatic Vegetation in the Pananualeng Beach Area, Sangihe Islands Regency - Yeni Indriani; Magdalin Ulaan; Numisye I Mose; Yessi A.P Manganang; Jetti T Saselah (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examined the ecological condition of aquatic vegetation in Pananualeng Beach, Sangihe Islands Regency, North Sulawesi, focusing on seagrass species composition, community dominance, and supporting water quality as key ecological indicators. Field observations were conducted in October 2025 at three purposively selected sampling stations using line-transect quadrats for seagrass assessment and in-situ measurement of temperature, salinity, dissolved oxygen, pH, and nutrients. The results showed that Thalassia hemprichii dominated the seagrass community, followed by Enhalus acoroides, indicating suitable habitat conditions and relatively stable aquatic vegetation. Water quality values were within acceptable seawater quality ranges, with no detected nitrate, nitrite, or ammonia. These findings indicate low anthropogenic pressure and support sustainable tourism management and seagrass conservation.